PENGARUH RELAKSASI OTOT PROGRESIF TERHADAP TINGKAT KECEMASAN PASIEN KEMOTERAPI DI RUMAH SINGGAH KANKER DENPASAR - Dian Praptini (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2014)
Cancer is one of diseases that can affects all the group of ages. Once a person has claimed has a cancer, the client will experience unfavorable conditions, such as psychological shock, anxiety, fear, confusion, sad, panic, insecure, or feeling alone and shadowed by death. Anxiety increases when the client visualize the changes in his life in the future as an effect of illness or as a result of treatment of a disease process. Progressive muscle relaxation is one of systematic technique that is designed to help relieving the muscle tension and decrease anxiety that occurs when someone’s conscious. The purpose of this research is to know the influence of progressive muscle relaxation on the anxiety level of patients with chemotherapy in the cancer home Denpasar. This research is quasi eksperiment with pretest and posttest design with control group. Sample retrieval using total sampling of 22 people. The treatment group given the progressive muscle relaxation during the three days that is done every morning and afternoon. The data collection was using the questionnaire Hamilton Anxiety Rating Scale (HARS) with ordinal scale. Based on statistical tests Mann-Whitney U Test with a 95% level of confidence gained value p = 0.002 (p<0.05) meaning that there are influences of progressive muscle relaxation on the level of anxiety. Based on the above findings, it is recommended to recommend this exercise to the patients as one of the techniques for reducing anxiety of patients undergoing chemotherapy.